Implementation of the Scaffolding Method in Improving Learning Outcomes of Asmaul Husana Material at MTS Nurul Qolbi Kota Tanah - Handoko, Yondi (ETNOPEDAGOGI: Jurnal Pendidikan dan Kebudayaan, 2024)
This study aims to determine the application of the scaffolding method in improving the learning outcomes of Asmaul Husna material at MTs Nurul Qolbi Kota Tanah. The scaffolding method is a learning approach that provides gradual support to students, starting from providing assistance to gradually decreasing along with the increase in student abilities. This study uses a qualitative approach with a descriptive method, where data is collected through observation, interviews, and documentation. The results of the study indicate that the application of the scaffolding method can improve students' understanding of the Asmaul Husna material. Through steps such as providing initial explanations, guiding students in understanding the meaning of each Asmaul Husna, and providing gradual exercises, students can memorize and understand the meaning of the names of Allah better. In addition, this method also motivates students to be more active and creative in learning. The results of the final test showed a significant increase in mastery of the Asmaul Husna material, with the majority of students achieving better scores than before the application of the scaffolding method. Therefore, the scaffolding method has proven effective in improving the learning outcomes of the Asmaul Husna material at MTs Nurul Qolbi Kota Tanah